Music of the highest class : elitism and populism in antebellum Boston - Broyles, Michael, 1939- (Yale University Press, 1992)
"There is a fundamental duality in American musical culture between classical music and vernacular music: the classical canon of great musical works seems to be surrounded by an aura of respectability that gives it a special mystique. In this book Michael Broyles examines this duality from a social-historical perspective, tracing its origins to early nineteenth-century Boston and showing how specifically American forces gave it a different profile from similar developments in Europe." "Broyles argues that in America music was considered merely entertainment until the beginning of the nineteenth century, when the positive moral effects of sacred music began to be recognized. By the 1830s the idea that secular symphonic music could also reflect positive moral values began to take hold. Broyles discusses the influence of various antebellum American groups on the growing idealistic conception of classical music: the hymnodic reformers, members of the evangelical middle class who established for the first time in America the idea that music could enrich; the socio-economic elite who elevated music by attempting to use it to establish cultural homogeneity; and the transcendental writers, who argued the moral superiority of abstract music. According to Broyles, Boston was at the heart of these developments, and he describes how, under the influence of musicians and civic leaders such as Lowell Mason, Samuel A. Eliot, and John S. Dwight, Bostonians of the 1840s enshrined the symphony orchestra as the institutional guardian of moral virtue."--Jacket